Ucaptama 1: nusantara, alam rumpun bangsa dan tamadun - Mohamed Yusoff, Mohamed Ghazali; Masri, Mawar (2025)
This paper is the text of Guest Speaker 1 (Ucaptama 1) presented by Adjunct Professor Dato’ Dr.Mohamed Ghazali Dato’ Mohamed Yusoff, Chairman of Lembaga Peradaban Melayu (ADAB) during the 15th Regional Symposium of The Malay Archipelago on 9 September 2024 at Kampung Budaya Warisan, Karai, Perak,Malaysia. The title “NUSANTARA, ALAM RUMPUN BANGSA DAN TAMADUN” was presented from the perspective of Lembaga Peradaban Melayu (ADAB), a Non-Government Organization (NGO) in Malaysia. The ADAB perspective is intended as a guide to the younger generation to understand from the perspective of “peradaban” or civilizational towards cultural-tradition resilience. The focus of the paper is comprehending the Alam Nusantara (Nusantara realm) from three dimensions: geographical; the race residing within the realm; tamadun and peradaban developed by the indigenous race of this realm. Highlighted as well ADAB’s perspective towards “budi” as an element of civilization resulting from the evolution of Nusantara societies’ values networks (umbaian). The text is written in the Malay language as it was presented in Malay.